2023
DOI: 10.1080/2162402x.2023.2212547
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of cancers by tumor antigen-expressing Staphylococcus epidermidis

Abstract: In a recent paper in Science, Chen et al . reported the genetic engineering of S. epidermidis expressing tumor cross-reactive antigens that trigger T cell responses and exhibit anticancer effects after topical administration. Here we discuss direct local effects and indirect systemic effects of exposure to engineered S. epidermidis strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Among them, skin microorganisms are a complex group containing bacteria, fungi, and viruses, which are involved in constituting the first protective barrier for humans 2 . It is worth mentioning that symbiotic bacteria have two roles that should not be overlooked: they are involved in the regulation of the local or systemic immune environment, and bacterial proteins can induce specific immune responses 3 . For instance, in 2012, a study reported that the skin microbiota can actively control local inflammatory responses and regulate resident T lymphocyte function 4 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Among them, skin microorganisms are a complex group containing bacteria, fungi, and viruses, which are involved in constituting the first protective barrier for humans 2 . It is worth mentioning that symbiotic bacteria have two roles that should not be overlooked: they are involved in the regulation of the local or systemic immune environment, and bacterial proteins can induce specific immune responses 3 . For instance, in 2012, a study reported that the skin microbiota can actively control local inflammatory responses and regulate resident T lymphocyte function 4 .…”
Section: Figurementioning
confidence: 99%
“…2 It is worth mentioning that symbiotic bacteria have two roles that should not be overlooked: they are involved in the regulation of the local or systemic immune environment, and bacterial proteins can induce specific immune responses. 3 For instance, in 2012, a study reported that the skin microbiota can actively control local inflammatory responses and regulate resident T lymphocyte function. 4 Moreover, utilizing the immune function of the body is one of the significant tumor therapies.…”
mentioning
confidence: 99%
“…The most effective approach combined soluble OT1 peptide with cell wall-anchored OT2 peptides, proving highly efficient in triggering immune responses against OVA-expressing B16F10 melanomas in mouse skin. Notably, the absence of either OT1 or OT2 from S. epidermidis , the absence of OVA from B16F10 melanomas, or the depletion of CD8 + T lymphocytes thwarted the observed anticancer effects, underlining the therapeutic potential of a cellular immune response targeting shared antigens between bacteria and cancer cells 74 .…”
Section: Introductionmentioning
confidence: 99%